2018
DOI: 10.1007/s42423-018-0022-4
|View full text |Cite
|
Sign up to set email alerts
|

Review of Solar Magnetic Sailing Configurations for Space Travel

Abstract: A solar magnetic sailing spacecraft utilizes the interaction between solar wind and magnetic field that is generated by a loop of superconducting wire attached onboard of the spacecraft. The development of the working principle of solar magnetic sailing from MagSail to magnetospheric plasma propulsion and magneto-plasma-sail is reviewed and discussed to study their performance, focusing on its operation for interplanetary travel. The orbital dynamic of MagSail is elaborated to explore the probable trajectories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Furthermore, electric sails and magnetic sails each have a well-defined upper limit corresponding to the typical speed of the solar/stellar wind, i.e., around 400 km/s, as higher spacecraft speeds would lead to a net deceleration instead. 12 Reviews of the magnetic and electric sail concepts can be found in [202] and [203].…”
Section: Electric Sails and Magnetic Sailsmentioning
confidence: 99%
“…Furthermore, electric sails and magnetic sails each have a well-defined upper limit corresponding to the typical speed of the solar/stellar wind, i.e., around 400 km/s, as higher spacecraft speeds would lead to a net deceleration instead. 12 Reviews of the magnetic and electric sail concepts can be found in [202] and [203].…”
Section: Electric Sails and Magnetic Sailsmentioning
confidence: 99%
“…The plasma magnet appears particularly encouraging in that it is able to interact with an enormous volume of the solar wind (e.g., tens to hundreds of km in extent) while only requiring a small antenna (e.g., meters) with modest power requirements. See [8] for a recent review of magnetic sail concepts. Magnetic sails are capable of only producing modest amounts of lift ( L D ≈ 0.3 [41,28]); they are predominately drag devices, more similar to parachutes than sails, which could be dragged up to the speed of the solar wind (≈ 700 km/s).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, numerous alternative technologies are being seriously pursued that do not require the on-board transport of fuel (Tajmar 2003). Examples in this category include light sails (Zander 1924;Forward 1984;McInnes 2004;Vulpetti 2012;Lubin 2016;Fu et al 2016), magnetic sails (Zubrin & Andrews 1991;Djojodihardjo 2018) and electric sails (Janhunen 2004;Janhunen et al 2010).…”
mentioning
confidence: 99%